The Sulfide/Silicate Coefficients of Nd and Sm: Geochemical “Fingerprints” for the Syn- and Epigenetic Cu-Ni-(PGE) Ores in the NE Fennoscandian Shield - Pavel A. Serov; Tamara B. Bayanova (Minerals, 2021)
One of the current directions of the Sm-Nd isotope systematics development is a dating of the ore process using sulfide minerals. Yet, the issue of the existence of rare earth elements (REE) in sulfides is still a matter for discussion. Sulfides from ore-bearing rocks of Proterozoic (2.53–1.98 Ga) Cu-Ni and platinum group elements (PGE) deposits of the Fennoscandian Shield were studied. It is found that the most probable source of REE in sulfide minerals from Cu-Ni-PGE complexes could be submicronic fluid inclusions, which are trapped at the mineral crystallization stage. In such a case, fluid or melt inclusions are specimens of the syngenetic parental melt, from which the base mineral formed, and these reflect a composition of the parental fluid. The mineral–rock partition coefficients for Nd and Sm can be used as “fingerprints” for individual deposits, and these are isotope-geochemical indicators of the ore-caused fluid that is syngenetic to sulfide. Moreover, the DNd/DSm ratio for various sulfide minerals can be used as a prospective geochemical tool for reconstructing a mineral formation sequence in ore complexes. On the other hand, differences in isotope compositions of sulfide neodymium could be markers of some ore-caused fluids and related to certain generations of sulfide minerals.